Reaffirming the Concept of Plurality in the Qur’an and its Practice in the Sunnah - Yongbao, Wang (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The main purpose of this article is to explore as well as analyse the concept of plurality in the Qur’an around four specific issues through the inductive methodology of analyzing literature. First, how does the Islamic civilization as founded on special beliefs, which differ from those that often force the ruled people to follow the beliefs of the ruling class to the greatest extent possible? Second, under the social pluralistic system of Islam, can all people, regardless of their religious background, ethnic identity, and racial color, be fully respected and protected? Third, can citizens live in Islamic countries freely survive, possess wealth, and actively contribute to society? Fourth, what is the ideology that has driven this pluralistic social governance system to continue for more than one thousand and four hundred years in Islamic countries? By discussing these issues, the conclusion drawn in this article is that the pluralistic ideology of Islamic society has been upheld and kept by the Islamic Worldview and Shari‘ah, which may lead and enable readers to gain a new understanding of Islam itself and its current situation as whole and the Muslim countries are the best in the world to practice plurality from the history up to now.